Sustainable LC3 Concrete in the Circular Economy: Assessment of Mechanical, Microstructural, and Durability Characteristics with Surkhi, Metakaolin, Nano‐Silica, and M‐Sand Blended Concrete - Badrinarayan Rath; Praveenkumar T R; Kavindra Singh Dhami; Prabhu Paramasivam; Mohamed Yusuf (Global Challenges)
Abstract Researchers are increasingly focused on eco‐friendly concrete with reduced carbon footprints. Among sustainable options, Limestone Calcined Clay Cement (LC3) concrete offers enhanced strength and durability with lower greenhouse gas emissions. This study evaluates the mechanical, microstructural, and durability characteristics of LC3 concrete modified with surkhi and nano‐silica as cementitious materials, replacing metakaolin and gypsum. Surkhi and nano‐silica are varied from 0%–40% and 0%–4%, respectively, while fine aggregate is completely replaced with M‐sand to improve packing density. Ten M30‐grade concrete mixes are analyzed after 28 and 90 days of curing. By incorporating surkhi and nano‐silica as partial replacements for metakaolin and gypsum in LC3 concrete, the research investigates potential improvements in strength, durability, and microstructural integrity of the concrete and provides lower greenhouse gas emissions compared to traditional Portland cement. Results revealed that surkhi and nano‐silica significantly improved strength and microstructure, with surkhi optimally limited to 30%. M‐sand proved effective in enhancing durability against weathering. These findings position modified LC3 concrete as a sustainable alternative, offering improved performance and advancing its potential within the circular economy framework.